The Potential of Silver-Doped Zinc Sulfide/Cadmium Sulfide Nanocomposites in Optoelectronic Applications - Maryam Hajiebrahimi; Sanaz Alamdari; Omid Mirzaee (Iranian Journal of Materials Science and Engineering)
Dual nanocomposites based on metal sulfide nanomaterials with a narrow band gap are favorable candidates for future optoelectronic applications and ionizing ray sensors. In this study, novel silver-doped zinc sulfide/ cadmium sulfide (ZnS/CdS: Ag) nanocomposites were synthesized using the cost-effective solvothermal approach. For the first time, the radiation sensitivity of the newly developed nanocomposite was assessed using a 241Am alpha source and ion beam-induced luminescence (IBIL) measurements. The ZnS/CdS: Ag nanocomposite demonstrated significant light emission in the blue-green spectrum when measured at room temperature. When exposed to alpha irradiation, the ZnS/CdS: Ag nanocomposite film displayed exceptional sensitivity compared to pure ZnS or CdS films. The FESEM images revealed a uniform distribution of semi-spherical and rod-shaped nanoparticles, with an average particle size measuring 180 nm. The results from XRD and EDX demonstrated distinct peaks corresponding to ZnS, CdS, and associated elements within the nanocomposite. The existence of several groups within the nanocomposite was confirmed through Fourier transform infrared spectroscopy. Evaluations revealed that the optical quality of the ZnS/CdS: Ag nanocomposite showed enhancement in comparison to pure ZnS and CdS. The results suggest that the ZnS/CdS: Ag nanocomposite film holds great promise for applications in optoelectronic devices and detection technologies.